Auxiliary selection is Agree - Irene Amato (Isogloss, 2022)
In this paper, I address the problem of auxiliary selection in Standard Italian and in Southern Italo-Romance varieties. In the former, the auxiliary depends on the argument structure, in the latter on the person feature of the subject. However, the features of the arguments play a crucial role even in languages where auxiliary selection is argument structure- driven. Therefore, I propose that auxiliary selection is the result of person Agree in both systems. Cross-linguistic variation is due to a single syntactic parameter (the ordering of the features on Perf) and to different inventories of vocabulary entries. In this contribution, I focus on Italo-Romance varieties, in particular on person-driven systems and on so-called mixed systems. I show that the apparently very different systems of auxiliary selection in Standard Italian and in Italo-Romance varieties are more similar than it seems: not only auxiliary selection in Italian is Agree for the person feature, but also many alleged person-driven varieties are indeed argument-structure-based systems.